Denoising Of ECG Signal Using Multi-Resolution Techniques Based On Stationary Wavelet Transformation With Different Coefficients (International Journal of Engineering and Computer Science, 2017)
Digitization of bio medical signals has brought a drastic change in analysis of signals. Electrocardiogram (ECG) is an important tool for the primary diagnosis of heart disease.ECG signal, the electrical interpretation of the cardiac muscle activity is very easy to interfere with different noises while gathering and recording. The ECG signal must be clearly represented and filtered to remove all noise and artifacts from signal. In this paper a new approach to filter the ECG signal from noise using Multi resolution Technique based on Wavelet Transform. This method gives better results than the other technique applied in this field.